EDUCATIONAL FIELD UNDER PERONISM 1946-1955 - Fiorucci, Flavia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paperwork studies the emergency impact during Peron’s regime in education life. It shows that schools were object of changes and transformations in those years in which executing them was limitated by an extremely conflictive environment. This article proves that education community reacted in several ways to this new political movement. Peron made political uses from education fact that also made education very conditionated by the confict. Education place and schools were the melting pot in which Aregentinean society was aware of the whole conflict.